Novel Technique of Pneumatic Posterior Capsulorhexis for Treatment and Prevention of Posterior Capsular Opacification - Ahmed M. Eid; Shaaban Abd-Elhamid Mehany Elwan; Ahmed M. Sabry; Hossam M. Moharram; Ashraf M. Bakhsh (Journal of Ophthalmology)
Purpose. To evaluate a new technique of posterior capsulorhexis using air support to treat primary posterior capsular opacification (PCO) during cataract extraction surgery or to prevent postoperative PCO. Setting. (1) Ophthalmology department, Faculty of Medicine, Minia University, 61519, El-Minia, Egypt. (2) Security Forces Hospital, Ophthalmology Department, Riyadh, Kingdom of Saudi Arabia. Design. Prospective, randomized, consecutive case comparative non controlled study. Methods. One hundred eyes of 100 patients with a mean age of 63.3 years with dense cataract were enrolled in the study. Fifty of them (group (1)) were with primary PCO (discovered during the operations) and fifty (group (2)) with clear posterior capsule. All of the patients underwent phacoemulsification and posterior capsulorhexis using the air to support the posterior capsule. Then, IOL implantations were done between the anterior and posterior capsular rims. Postoperatively, each patient was evaluated for the following: visual acuity (UCVA and BCVA), manifest refractive spherical equivalent (MRSE), intraocular pressure, intraocular lens (IOL) stability, visual axis opacification, and posterior segment complications as retinal breaks, retinal detachment, or cystoid macular edema (CME). Results. There were no significant differences in UCVA, BCVA, and MRSE. All cases had a clear visual axis, with stable IOL and normal IOP during the follow-up period without posterior segment complications. The VA improved significantly throughout the follow-up periods in both groups without significant clinical difference. Conclusion. Pneumatic posterior capsulorhexis is a new effective technique for the treatment of primary PCO in dense cataract and for prevention of postoperative PCO with the good visual outcomes and minimal complications. This trial is registered with NCT04007965.